The Influence of Canvas-to-Screen Art on Contemporary Animation - Zhao, Siyi (Transactions on Social Science, Education and Humanities Research, 2024)
This paper discusses the important role of fine art in contemporary animation and its far-reaching influence. By sorting out the historical origin of fine arts and animation, analysing the performance of fine arts in contemporary animation, examining the role of technological progress in promoting animation fine arts and analysing it with classic cases, it reveals the core position of fine arts in animation creation. Fine art not only provides a unique visual language and style for animation, but also expands the means of expression and dissemination of animation through the progress of technology and the application of new media. This paper argues that the development of contemporary animation fine art presents a trend of diversification, cross-border and individualisation, which not only enriches the artistic expression of animation, but also promotes the continuous innovation and prosperity of the animation industry.